2021
DOI: 10.1155/2021/6620677
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Natural Antioxidants Improve the Vulnerability of Cardiomyocytes and Vascular Endothelial Cells under Stress Conditions: A Focus on Mitochondrial Quality Control

Abstract: Cardiovascular disease has become one of the main causes of human death. In addition, many cardiovascular diseases are accompanied by a series of irreversible damages that lead to organ and vascular complications. In recent years, the potential therapeutic strategy of natural antioxidants in the treatment of cardiovascular diseases through mitochondrial quality control has received extensive attention. Mitochondria are the main site of energy metabolism in eukaryotic cells, including myocardial and vascular en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 203 publications
(107 reference statements)
2
23
0
Order By: Relevance
“…Five compounds were identified by different extraction methods: ferulic acid, ginsenoside Rb1, astragaloside IV, diosgenin, and catalpol ( Figure 6 ). Studies have reported that the above five active ingredients from TYHX can play a good therapeutic effect in different types of cardiovascular diseases [ 20 , 23 ]. Moreover, it can protect many kinds of cells (including endothelial cells, cardiomyocytes, and sinoatrial node cells) under stress conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five compounds were identified by different extraction methods: ferulic acid, ginsenoside Rb1, astragaloside IV, diosgenin, and catalpol ( Figure 6 ). Studies have reported that the above five active ingredients from TYHX can play a good therapeutic effect in different types of cardiovascular diseases [ 20 , 23 ]. Moreover, it can protect many kinds of cells (including endothelial cells, cardiomyocytes, and sinoatrial node cells) under stress conditions [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported that the above five active ingredients from TYHX can play a good therapeutic effect in different types of cardiovascular diseases [ 20 , 23 ]. Moreover, it can protect many kinds of cells (including endothelial cells, cardiomyocytes, and sinoatrial node cells) under stress conditions [ 20 ]. The protective mechanism may be closely related to the mitochondria quality control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, severe diabetic cardiomyopathy with heart failure is accompanied by myocardial hypertrophy, partial myocardial ischemia, and hypoxia [36,53]. The energy metabolism of myocardial cells is converted from fatty acid oxidation to glycolysis to adapt to hypoxia as a selfprotective mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cholesterol’s ability to early impair vascular health is also mediated by its oxidation [ 6 ]. A number of dietary components exert an antioxidant effect on LDL and on endothelium that is strongly sensitive to exposure to the positive action of antioxidants [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%